2016
DOI: 10.1097/spv.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Osteomyelitis After Robotic Sacrocolpopexy

Abstract: Sacral osteomyelitis is a rare complication following RASC and may present only as back pain without constitutional symptoms. Intravenous antibiotics and surgical excision of sacral mesh are routinely performed, but preservation of vaginal mesh is a viable option. The clinician should have a high index of suspicion for osteomyelitis in any patient who presents with back pain after RASC, regardless of absence of other presenting symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The anterior longitudinal ligament thickness over the promontory is only 1.9 mm where penetration of the periosteum is more likely to happen [ 19 ]. For the reason above, spondylodiscitis after sacrocolpopexy has been reported [ 14 , 20 , 21 ]. It is a rare but devastating complication for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior longitudinal ligament thickness over the promontory is only 1.9 mm where penetration of the periosteum is more likely to happen [ 19 ]. For the reason above, spondylodiscitis after sacrocolpopexy has been reported [ 14 , 20 , 21 ]. It is a rare but devastating complication for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction from PubMed provided a total of 36 abstracts, and further reference search yielded additional 8 articles, gathering a total of 52 cases, 6 7 8 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 including ours. The summary of the results is presented in Tables 1 and 2 .…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6 In one study, spondylodiscitis was found postoperatively in 5.6% of patients after laparoscopic sacrocolpopexy with concomitant rectopexy and in 0% of patients after laparoscopic sacrocolpopexy without rectopexy. 5 Some authors have even suggested that the graft rejection process could be an initiator or promotor of the inflammatory process in sacral bone after this procedure. 12 Combined surgical and antimicrobial therapy is the treatment of choice in most cases of spinal epidural abscess.…”
Section: Discussionmentioning
confidence: 99%
“…2 Spinal infection after abdominal or laparoscopic sacrocolpopexy is a rare complication. [3][4][5][6][7] The most common causative pathogen in spinal epidural abscess overall is Staphylococcus aureus (60%), whereas anaerobic microorganisms are only rarely found (2%). 8,9 Bacteroides spp are anaerobic, non-spore-forming, Gramnegative rods with a tendency of abscess formation.…”
Section: Introductionmentioning
confidence: 99%